DEPRESSION LEVELS AMONG ELDERLY RESIDENTS IN A SOCIAL CARE INSTITUTION: A DESCRIPTIVE STUDY - Karisatil A'la, Erna; Andas, Amzal Mortin; Prima, Ashar; Lanahdiayanna, Lu'lu'a (Nursing Genius Journal, 2025)
Background:  Depression is a common mood disorder among the elderly, particularly those living in social care institutions. Factors such as social isolation, loss of family support, and chronic health conditions contribute to increased vulnerability. Understanding the level and characteristics of depression in this population is essential for developing targeted interventions. Purpose:This study aimed to describe the level of depression and its demographic characteristics among elderly residents at Tresna Werdha Budi Mulia 1 Social Care Institution. Methods:  A quantitative descriptive design was used with 162 elderly residents selected through purposive sampling. Data were collected using the Geriatric Depression Scale-15 (GDS-15) and a demographic questionnaire. Univariate analysis was performed using SPSS version 22.   Results:   The majority of respondents were female (59.3%), aged 60–74 years (66.7%), widowed (66.0%), and had a high school education (65.4%). Mild depression was the most prevalent (43.8%), followed by moderate depression (35.2%). A small proportion experienced severe depression (7.4%). Hypertension was the most common health complaint (45.7%).   Conclusion: Mild depression is prevalent among institutionalized elderly. Factors such as gender, marital status, length of stay, and health conditions may influence depression levels. These findings highlight the need for mental health screening and psychosocial support programs in elderly care institutions.